The promise of land : undoing a century of dispossession in South Africa - Hendricks, Fred T.; Ntsebeza, Lungisile; Helliker, Kirk. (Auckland Park, South Africa : Jacana Media, 2013)
"The ongoing racialised inequalities in land, inherited from colonial dispossession, act as a spatial barrier to imagining a unitary nation in contemporary South Africa. The starting point for this book is that the current land reform policies in the country fail to take this colonial context of division and exclusion into account. Consequently, there is an abiding crisis in land in South Africa. The book examines the very many dimensions of this crisis in urban areas, commercial farming areas and communal areas. It argues for a fundamental change in approach to move beyond the impasse in both policy and thinking about land. The Promise of Land argues that social movements have a critcal role to play in charting a new course, both in respect of access to land and in influencing broader policy options. Struggles from below are crucial for rethinking purely statist efforts at land reform and the book grapples with the interplay between oppositional campaigns of social movements and the state's policies and responses." -- Back cover.
Includes bibliographical references and index.
Keywords: Land tenure -- South Africa; Land reform -- Government policy -- South Africa; Social movements -- South Africa; Land settlement -- South Africa; Restitution -- South Africa; Agriculture -- South Africa; Land use, Rural -- South Africa; Rural development -- South Africa